Person-environment relationship, urban sustainability and public policies in the coronavirus pandemic: literature review - Araujo Junior, Antonio Cesar Peixoto de; Araujo, Barbara Peixoto de; Penachiotti, Fabiane Dolphine Fuentes; Lizama, Maria de Los Angeles Perez; Grossi-Milani, Rute (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The COVID-19 pandemic has significantly affected urban habits around the world and, in the face of social isolation and other sanitary measures taken, there are concomitant benefits to the urban environment. The current study seeks to analyze the scientific literature on the person-environment relationship, in the urban context, during the coronavirus pandemic. An integrative literature review was carried out, based on the search for scientific articles in the Web of Science (WOS), ScienceDirect and PubMed databases, from January 2020 to January 2022. An integrative literature review was carried out, based on the search for scientific articles in the Web of Science (WOS), ScienceDirect and PubMed databases, from January 2020 to January 2022. Three combined keywords, in English, were used for the selection of articles: environmental perception, environmental concern and Covid-19. The results showed that the sustainable urban environment was important for better coping with the pandemic, especially in the period of social isolation, in which contact with the green environment provided an increase in urban resilience. It is concluded that the strengthening of the person-environment relationship and socio-environmental responsibility represent a promising strategy to build a greater commitment of society to the environment after facing the covid-19 crisis.
Keywords: Covid-19; Environmental perception; Environmental concern; Urban green space; Well-being